Case Report: First use of dental bisphenol A-glycidyl methacrylate composite without UV light polymerization for repair of iatrogenic CSF leak following a frontal craniotomy plus tumor resection - Oumarou, Haman Nassourou; Orlane, Ndome Toto (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to evaluate the efficacy and safety of bisphenol A-glycidyl methacrylate (bis-GMA) without UV light polymerization for the repair of refractory iatrogenic cerebrospinal fluid (CSF) leaks with large skull base defects.BackgroundCSF leakage remains a common complication after neurosurgical interventions with a substantial resultant impact on morbidity and increased healthcare costs. The management of refractory CSF leaks with large skull base defects remains challenging. Radiological investigations are highly contributive as they visualize the defect and assess the herniated content. Optimal treatment depends on the breach parameters and the consequent hernia. Surgery, when indicated, consists of exposure of the defect and its reconstruction using different grafts. The dental composite bis-GMA has been investigated and has shown effectiveness for the repair of anterior skull base defects. This is due to its compactible mechanical properties, long-term stability, and good osteo-integration. Hence, it presents a promising solution for refractory CSF leaks not responding to extradural endoscopic techniques.Case reportWe describe the case of a 40-year-old female with persistent CSF rhinorrhea following a left frontal craniotomy performed 4 years before. A high-resolution cerebral CT scan and MRI revealed a bilateral fronto-ethmoidal osteo-meningeal breach and a hyperintense T2 signal in the ethmoidal sinus interrupting the hypo-intensity of the bone, respectively. In our patient, surgical treatment involved a bifrontal craniotomy and osteo-meningeal reconstruction with the use of bis-GMA without UV light polymerization. This reconstruction gave rigid structural support and watertight closure of the defect. Postoperatively, the CSF rhinorrhea ceased and there were no perceivable associated complications.ConclusionGiven the favorable outcome, the composite bis-GMA without UV light polymerization can be used as a reliable material for the repair of iatrogenic CSF leaks.